Students’ Perception Toward English Meeting Club of Their Speaking Skill - Harzanah, Novi Dwi; Islam, Muhammad Hifdil; Hamdany, Beny (Journey: Journal of English Language and Pedagogy, 2024)
This research aims to assess the students' perceptions of English meeting club of their speaking in the language. Istiqlal Islamic Boarding School's English class chose three students to participate in the research. The researchers used a descriptive qualitative method and collected data using two steps: an observational and an interview. The result of this research is majority of students in this research had a positive perception of English meeting club. The students are believing that by joining the English club, they would be able to improve their speaking skills. Another thing the student thought would help them improve their communication skills, especially their pronunciation, was going to English club meetings. On top of that, it might stand in for students who have problems with public speaking fear and low confidence